PENGARUH PERIODE BEBAS GULMA TERHADAP PERTUMBUHAN TEBU (Saccharum officinarum L.) - Hidayat Pujisiswanto; Kadek Wijaya Kusuma; Rusdi Evizal; Herry Susanto (JURNAL AGROTROPIKA, 2026)
Sugarcane is one of the main crops in the plantation sector in Indonesia which has high economic value in sugar industry. One of the factors that disrupts the growth and yield of sugar cane is the interference of weeds during the cultivation period. The aim of this research was to determine the growth of sugarcane in response of a weed-free period. The research used a Randomized Complete Block Design (RCBD) with 6 treatments and 4 replications. The treatments are free from weeds along 3 months after planting (MAP), free from weeds along 6 MAP, free from weeds along 9 months MAP, weedy along 3 MAP, weedy 6 MAP, and weedy along 9 MAP. Observations were made on weed growth and vegetative growth of sugarcane until 9 MAP. The data obtained were analyzed using analysis of variance and continued with the Least Significant Difference (LSD) test at 5% level. The analysis found that the dominant weeds in sugarcane plantations at the research location were grasses, namely Brachiaria mutica, Digitaria ciliaris, and Paspalum conjugatum. Furthermore, we concluded that the weed-free period increases sugarcane germination and growth. At 9 months after planting, weed-free sugarcane for 9 months and weeded sugarcane for 3 months produced the highest sugarcane populations, reaching 83,949 and 78,952 per hectare, respectively. The highest stem diameter was obtained in weed-free for 3, 6, and 9 months after planting. The highest sugarcane were obtained in weed-free for 3, 6, and 9 months after planting, and in weedy for 3 months after planting. Weed control during the 3-6 months after planting increased sugarcane germination, population, stem diameter, and plant height. The critical period for weed control in sugarcane ranges from 2 to 6 months after planting. Keywords: critical period, weeding, weeds, sugarcane